Temporalidades inter/disciplinares (Derecho, Filosofía, Política) - Bermejo Castrillo, Manuel Angel; Alvarez Cora, Enrique; Bares Partal, Juan de Dios; Bermejo, Castrillo, Manuel Angel; Cubo Ugarte, Oscar; Müller, Ernst; Oncina Coves, Faustino; Picht, Barbara; Sánchez Fernández, José Manuel; Schmieder, Falko (Historia del derecho, 2021)
This book is the result of a number of personal, academic and scientific confluences between scholars from different fields who, following on from previous fruitful synergies, have now been brought together to reflect jointly on a decisive factor in their respective fields of study: temporality. The so-called conceptual history harbours in its matrix a theory of historical times, in which the relationship of attraction and repulsion between history and memory is already proverbial. The collective endeavour in this volume, which focuses on inter/disciplinary temporalities, is based on an affinity of transversal interests and is encouraged by a sustained intention to build bridges between different areas of knowledge and to break their traditional self-referential inertia. The temporal dimension of justice, in its different declinations, has often been pretermitted or implicitly presupposed, without emerging as a theme in an explicit way, and yet it is susceptible to meditation from a plurality of perspectives: ethical, legal, sociological, political, historical, philosophical